Radiation resistance of metal-glass coatings for floating composite structures = Радиационная стойкость металлостеклянных покрытий для плавучих композитных сооружений - Kazimirenko, Yu. A.; Казимиренко, Ю. А.; Shlapatskaya, V. V.; Шлапацкая, В. В. (My University, 2015)
The article discusses the prospects of application of new metal and glass electric arc coatings made of Sv-08G2C and Sv-AMg5 filled with hollow glass microspheres, powders, liquid silicate and the leaded glass for protection of steel structures from γ-radiation. The purpose of study is to investigate the radiation resistance of metal and glass coatings under γ-radiation Co60. Physical and mechanical properties of the coatings and coated steel samples made of St3 are experimentally studied: microhardness, tensile strength and yield strength. Structural and phase changes are studied using the methods of electronic and optical microscopy, an X-ray analysis. The influence of glass excipients on the stability of the structure and properties of coatings under γ-radiation is noticed. A qualitative comparison of metal-glass coatings to traditionally used lead-containing materials is performed. It is found out that under the influence of γ-radiation of Co60 with the electron energy E = 2.0, 4.5 MeV in electric arc metal-glass coatings there is no structural and phase transitions and the irradiation process is accompanied by surface hardening, coated steel plates made of St3 preserve stable mechanical properties. The study results can be applied for designing the protection against γ-radiation for technical equipment, energy facilities and transport. = Исследовано влияние γ-излучения Со60 на структуру и механические свойства композиционных электродуговых покрытий на основе Св-08Г2С и Св-Амг5, наполненных полыми стеклянными микросферами, порошками натрийсиликатного и свинцовосодержащего стекол. Показаны перспективы применения покрытий в составе конструкций плавучих композитных сооружений для перевозки и хранения радиоактивных веществ низкой и средней активности.
Казимиренко, Ю. А. Radiation resistance of metal-glass coatings for floating composite structures = Радиационная стойкость металлостеклянных покрытий для плавучих композитных сооружений / Ю. А. Казимиренко, В. В. Шлапацкая // Shipbuilding & Marine Infrastructure. – 2015. – № 1 (3). – C. 111–121.
Keywords: floating composite structures; radiation resistance; γ-radiation; electric arc coatings; structure; mechanical properties; плавучие композитные сооружения; радиационная стойкость; γ-излучения; электродуговые покрытия; структура; механические свойства